Asymmetric organocatalytic synthesis of tertiary azomethyl alcohols: key intermediates towards azoxy compounds and α-hydroxy-β-amino esters. Issue 14 (15th March 2017) - Carmona, José A.; Gonzalo, Gonzalo de; Serrano, Inmaculada; Crespo-Peña, Ana M.; Šimek, Michal; Monge, David; Fernández, Rosario; Lassaletta, José M.
Abstract : New carbohydrate based organocatalysts have been developed for the asymmetric nucleophilic addition of formaldehyde tert -butylhydrazone to α-keto esters. Abstract : A series of peracylated glycosamine-derived thioureas have been synthesized and their behavior as bifunctional organocatalysts has been tested in the enantioselective nucleophilic addition of formaldehyde tert -butyl hydrazone to aliphatic α-keto esters for the synthesis of tertiary azomethyl alcohols. Using the 1, 3, 4, 6-tetra- O -acetyl-2-amino-2-deoxy-β-d -glucosamine derived 3, 5-bis-(trifluoromethyl)phenyl thiourea the reaction could be accomplished with high yields (75–98%) and moderate enantioselectivities (50–64% ee). Subsequent high-yielding and racemization-free tranformations of both aromatic- and aliphatic-substituted diazene products in a one pot fashion provide a direct entry to valuable azoxy compounds and α-hydroxy-β-amino esters.